Is Business Life a Journey or RAFTING ON THE RAGING RIVER RAPIDS? Lee Iacocca’s Story - Jezic, Daniela; Juretic, Ksenija; Kastelan, Kristina (International Journal of Language and Literary Studies, 2025)
In today’s business world, our activities have turned into RAFTING ON THE RAGING RIVER RAPIDS where the dynamic flow shapes our identity, aspirations and future, creating a cyclical pattern driven by our desire for success and fear of failure. To make abstract concepts like time, success, and failure more tangible, we translate them into "semantically grounded" concepts based on physical experiences reflected in conceptual metaphors. A business career, often conceptualized through the metaphor LIFE IS A JOURNEY, becomes a framework for analyzing Lee Iacocca’s notable career at Ford and Chrysler in this paper. Since metaphorical mappings are rarely identical across languages, we investigated the English original metaphors and image schemas in Lee Iacocca’s autobiography and their Croatian translations. The autobiography discusses success and failure, the ups and downs of business where UP always carries positive attributes, and DOWN represents negative trends and failure. Therefore, Iacocca uses image schemas such as Climbing UP to depict the start of his prosperous business career, being ON TOP of the World to describe his enormous success, and a FALL from MOUNT EVEREST to depict his failure.